Theme: An Approach for Aspect-Oriented Analysis and Design - Baniassad, Elisa; Clarke, Siobhan (International Conference on Software Engineering: Proceedings of the 26th International Conference on Software Engineering; 23-28 May 2004, 2004)
Aspects are behaviours that are tangled and scatteredacross a system. In requirements documentation, aspectsmanifest themselves as descriptions of behaviours that areintertwined, and woven throughout. Some aspects may beobvious, as specifications of typical crosscutting behaviour.Others may be more subtle, making them hard to identify. Ineither case, it is difficult to analyse requirements to locateall points in the system where aspects should be applied.These issues lead to problems achieving traceability of aspectsthroughout the development lifecycle. To identify aspectsearly in the software lifecycle, and establish sufficienttraceability, developers need support for aspect identificationand analysis in requirements documentation. To addressthis, we have devised the Theme approach for viewingthe relationships between behaviours in a requirements document,identifying and isolating aspects in the requirements,and modelling those aspects using a design language. Thispaper describes the approach, and illustrates it with a casestudy and analysis.